Pharmacoecomonic study of oral antidiabetic drugs available in Indian pharmaceutical market - Wadagbalkar, Prashant; Bhadoriya, Sandeep Singh (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Diabetes mellitus is a metabolic disorder requiring lifelong medication which further adds to comorbidity. Cost of the drug pays an important role in adherence and compliance to the treatment. There is a wide variation in prices of oral hypoglycemic drugs available in Indian pharmaceutical market. Aims and objectives of the study was planned to evaluate cost of oral antidiabetic drugs of various brands currently available in Indian market either as single drug or in combination. Methods: Cost of antidiabetic medications manufactured by various pharmaceutical companies in the same strength and dosage form was obtained from the price list provided by various pharmaceutical companies in current index of medical specialties December 2022-March2023. The cost ratio and percentage price variation for each formulation was calculated and analyzed. Results: Among single antidiabetic drugs, Tab. Metformin 500 mg shows highest percentage price variation (809%) and highest cost ratio (9.09). Among fixed dose combinations, Tab. Glibenclamide 5 mg + Tab. Metformin 500 mg shows highest percentage price variation 300.8% and highest cost ratio 4. Conclusions: Our study shows that there is high price variation for oral anti diabetics. It is important to bring awareness about wide variation in prices so that drug cost can be reduced and made affordable to common man which plays major role in compliance of patient.